Massive Acromioclavicular Joint Cyst with Intramuscular Extension: Case Report and Review. (10th June 2018) - Zhang, Yiyang; Old, Jason
Abstract : Acromioclavicular cysts are an uncommon manifestation secondary to a massive rotator cuff tear and/or a degenerative osteoarthritic AC joint. We present a case of an 80-year-old female with a symptomatic acromioclavicular cyst that extended intramuscularly into the trapezius. She did not complain of symptoms associated with a massive rotator cuff tear; however, the cyst has been increasing in size and she was interested in having it removed. Intraoperatively, the mass extended into the trapezius muscle and was removed en bloc after dissecting it down to the stalk. A distal clavicle excision was then performed using an oscillating saw. After the cyst was excised, it was incised revealing thick mucoid content. The patient did well postoperatively at the three-month follow-up without signs of recurrence. To our knowledge, this is the first case of AC joint cyst with intramuscular extension that was managed operatively.